Accidental haemorrhage in third trimester: maternal and fetal outcome - Chavan, Niranjan N.; Rohidas, Vibhusha; Waikule, Hanumant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abruptio placenta or accidental haemorrhage is one of the obstetrical emergencies and is truly accidental with few warning signs. Present study is planned to study the maternal and fetal outcome in patients of abruption placenta in a tertiary care referral hospital in a rural set up which is helpful to plan management strategies and to decrease mortality and morbidity. Methods: A prospective observational study was conducted at Department of Obstetrics and Gynaecology at tertiary care centre during September 2015 to August 2019. A total of 270 cases of abruptio placenta coming to the labor ward and delivered were included in the study. The information collected regarding maternal and fetal parameters were recorded in a master chart in Microsoft Excel 2010 and analyzed using the statistical package for the social sciences software (SPSS) version 20.0. Results: In the present study there were a total of 29887 deliveries with 270 cases of abruptio placenta, incidence being 0.9%. Bleeding per vagina is the most common presentation (85.6%) followed by pain abdomen (70.7%). Common risk factors for accidental hemorrhage were: Pre-eclampsia (39.6%) and anaemia (32.2%). Rate of cesarean section was 40.7% (n-110) while rate of forceps delivery was 4.8% (n-13). Associated maternal complications include: post-partum hemorrhage (18.9%), DIC (10%), acute renal failure (4.1%) and puerperal sepsis (1.9%) while maternal mortality rate was 1.9%. Low birth weight (<2.5kg) was observed in 74.8% cases while still birth and neonatal mortality rate was 35.2% and 12.6% respectively. Conclusions: Abruptio placenta or accidental hemorrhage is major risk factor for maternal and perinatal morbidity and mortality, thus efforts should be taken to reduce risk factor for abruptio placenta. Strengthening of antenatal care, anticipation and evaluation of associated high-risk factor and prompt management of complication can improve maternal and perinatal outcome in these cases. Abruptio placenta should be managed in centers where there is advanced maternal and neonatal health care facilities are available.